(untitled) (Research, Society and Development, 2022)
The coronavirus disease (COVID-19) manifests symptoms in the most diverse systems of the individual, such as, for example, tachycardia, chest pain, loss of muscle mass, fatigue, cough and decreased functional capacity. Considering the severity of the dysfunctions observed in patients, it is extremely important that they receive adequate treatment. In this way, the physical therapist is active both in the prevention and in the rehabilitation of pulmonary diseases and functional limitations present in the individual’s activities of daily living (ADL’s). The present study aims to describe the experience of academics regarding the cardiorespiratory rehabilitation of post-COVID-19 patients. Methodologically, this article was an experience report on the performance of academics from the Physiotherapy outpatient internship, in the cardiorespiratory rehabilitation of patients with post-COVID-19 sequelae who were treated at the outpatient clinic of a university in the interior of the Amazon. The study reported on the experiences of academics involved in such care, through their reports regarding the characterization of the rehabilitation environment and the public served, as well as on their performance in the first evaluation of patients, and also the description of the care and results obtained. generally in the rehabilitation process. It is considered that the period of care contributed significantly to the training of academics, as well as to the cardiorespiratory and emotional improvement of the welcomed public.